THE EFFECT OF WORK STRESS ON JOB SATISFACTION WITH WORK MOTIVATION AS A MEDIATING VARIABLE - Kadek Gata Satya Darma Parta Putra; I Gusti Made Suwandana (Riviera Publishing, 2024)
The background of this research stems from an understanding of the crucial role job satisfaction plays in influencing employee performance and productivity. Job satisfaction fosters a positive work environment and motivates employees to contribute more effectively. Work motivation is also vital in achieving sales targets with sub-agents or salespeople. Incentives like bonuses support their enthusiasm. However, work-related stress also requires attention as it can negatively impact job satisfaction and performance. This study considers work-related stress as a factor affecting job satisfaction and views work motivation as a mediating variable linking work-related stress and job satisfaction. Through this analysis, the research aims to understand the intricate relationship between work-related stress, work motivation, and job satisfaction at PT. Windhu Sari Gas Batubulan Branch. This research employs a saturated sample determination method with primary data collected through interviews, questionnaires, and observations at PT Windhu Sari Gas Batubulan Branch. The analysis encompasses descriptive analysis and path analysis. The results indicate that 1) work-related stress significantly and negatively influences job satisfaction, 2) work motivation significantly and negatively affects job satisfaction, 3) work-related stress significantly and negatively influences work motivation, and 4) work motivation mediates the influence of work-related stress on job satisfaction. Based on these findings, the management of PT. Windhu Sari Gas Batubulan Branch is advised to enhance job satisfaction by considering work-related stress and work motivation.